The Effect of Repetitive Kicking on Balance and Agility in Pencak Silat Athletes of PSHT Mantup Branch - Dimas Ferdiansyah Putra; Luqmanul Hakim (Green Publisher Indonesia, 2026)
This study aims to analyze the effect of repetitive front kick exercises on the balance and agility of Pencak Silat athletes from Persaudaraan Setia Hati Terate (PSHT), Rayon Mantup. The research employed a quantitative experimental method with a one-group pretest-posttest design. A sample of 28 athletes was selected using purposive sampling technique. Measurement instruments included the Standing Stork Test for balance and the T-Test TPS for agility. Data were analyzed using normality tests, homogeneity tests, and paired t-tests. The results of normality and homogeneity tests indicated that the data were normally distributed and homogeneous. The t-test yielded a significance value of 0.000 for both variables, which is less than 0.05, leading to the acceptance of the research hypothesis. The findings demonstrate that repetitive front kick training significantly improves both balance (t_calc = -9.686) and agility (t_calc = 11.180) of the athletes. This improvement is attributed to the characteristics of fast and repetitive movements that train body control and neuromuscular coordination. The study recommends integrating repetitive kick exercises into PSHT training programs to optimize athlete performance.